Application of the Inquiry Learning Model in Throwing and Catching Games to Enhance Students’ Critical Thinking Skills at SDN Pualam Sari 3 - Firmansyah, Yoga; Rakhman, Arie; Anggara, Norma; Rahmadi, Rahmadi (Empiricism Journal, 2026)
The development of critical thinking skills has become an important objective in physical education, as learning activities frequently emphasize motor performance while providing limited opportunities for higher-order cognitive engagement. In the context of catch-and-throw game instruction, students are often required to execute movement skills without being sufficiently encouraged to analyze situations, evaluate alternatives, or make reasoned decisions during learning activities. This study therefore investigated changes in students’ critical thinking skills following the implementation of an inquiry-based learning model in physical education classes at SDN Pualam Sari 3. A quantitative approach was adopted using a pre-experimental one-group pretest–posttest design. The participants consisted of 30 students selected through total sampling. Critical thinking ability was assessed using a Higher Order Thinking Skills (HOTS)-oriented test instrument that had previously met validity and reliability criteria. Data were collected before and after the intervention and subsequently analyzed using descriptive statistics and a paired-samples t-test with a significance level of 0.05. The findings demonstrated a substantial improvement in students’ critical thinking performance after the learning intervention. The mean score increased from 59.33 on the pretest to 91.00 on the posttest, representing an average gain of 31.67 points. Statistical analysis further confirmed that the difference between the two measurements was significant, t(29) = −28.027, p < .001. These results indicate that the use of the inquiry learning model was associated with enhanced critical thinking skills in catch-and-throw game learning activities. Although the findings provide empirical support for the potential educational value of inquiry-based instruction in physical education, the absence of a comparison group limits the strength of causal interpretation. Future studies are therefore encouraged to employ more rigorous experimental designs involving control groups and broader participant populations to obtain stronger evidence regarding the effectiveness of the intervention.